Nanoscale subsurface imaging. (24th March 2017) - Soliman, M; Ding, Y; Tetard, L
Abstract: The ability to probe structures and functional properties of complex systems at the nanoscale, both at their surface and in their volume, has drawn substantial attention in recent years. Besides detecting heterogeneities, cracks and defects below the surface, more advanced explorations of chemical or electrical properties are of great interest. In this article, we review some approaches developed to explore heterogeneities below the surface, including recent progress in the different aspects of metrology in optics, electron microscopy, and scanning probe microscopy. We discuss the principle and mechanisms of image formation associated with each technique, including data acquisition, data analysis and modeling for nanoscale structural and functional imaging. We highlight the advances based on atomic force microscopy (AFM). Our discussion first introduces methods providing structural information of the buried structures, such as position in the volume and geometry. Next we present how functional properties including conductivity, capacitance, and composition can be extracted from the modalities available to date and how they could eventually enable tomography reconstructions of systems such as overlay structures in transistors or living systems. Finally we propose a perspective regarding the outstanding challenges and needs to push the field forward.